Uma análise do movimento de constituição da ementa da disciplina de álgebra linear na licenciatura em matemática - Ribeiro, Luciane Nunes (2018)
This research analyzes the constitution's movements of the University in Europe and in Brazil; the creation of Mathematics’ first course in Brazil; the constitution of the contents which make up the Linear Algebra discipline syllabus and, finally, its current discipline syllabus in the presential courses in Mathematics Degree of the Brazilian Federal Universities. The purpose of the mentioned analysis is to answer the following research question: how did occur the contents' constitution that compose the syllabus of Linear Algebra in Mathematics degrees of Brazilian Federal Universities? In order to reach this objective, the bibliographical and documentary study were used as methodology, especially classical, history and yearbooks, legislation and the syllabus. The theoretical reference is based on Historical-Cultural Theory assumptions, which is scientific, but also political (MOURA, 2017; VYGOTSKI, 1995; CEDRO, 2008; OLIVEIRA, 2002; ZANELLA, 2007), through the study of logical- historical movement – defended by Kopnin, 1978; Sousa, Panossian, Cedro, 2014; Sousa, 2004; Fazenda, 2000 – of Algebra Linear discipline constitution, according to Pires, 2006; Dorier, 2000, Silva, 2003; Moore, 1995. It was necessary to understand the reasons of its inclusion in the university context and its contribution to the professional formation of Mathematics teacher, according to Bastos (1980; 2006), Boyer (1974), Cavalari (2012), Celestino (2000), Garding (1981), Kopnin (1978), Caraça (1959), Ríbnikov (1987), Tubino (1984), Kleiner (2007), among others. It was analyzed 55 Federal Brazilian Universities that offer presential course of Degree in Mathematics. As categories of analysis were stablished the content of syllabus, the workload and the basic bibliographic reference of compulsory discipline of Linear Algebra of these institutions. As more relevant conclusions, it was observed that Linear Algebra began to be developed and taught in Universities to solve practical problems of diverse intellectuals of engineering and exact sciences, and that the transfer of its indexes in an unrelated way may contribute to the difficulties in teaching and learning process present in this discipline.